Cardiomyopathy Associated with Celiac Disease in Childhood. (10th October 2012) - Boskovic, Aleksandra; Kitic, Ivana; Prokic, Dragan; Stankovic, Ivica
Abstract : Celiac disease is predominantly a disease of the small intestine characterized by chronic malabsorption in genetically susceptible individuals who ingest grains containing gluten, such as wheat, barley, and rye. Although previously believed to be uncommon, celiac disease may be present in up to 1% of the adult and children population. Celiac disease is associated frequently with iron-deficiency anemia, dermatitis herpetiformis, selective IgA deficiency, thyroid disorders, diabetes mellitus, and various connective tissue disorders but is rarely associated with cardiomyopathy.